Cardiovascular risk in advanced naïve HIV-infected patients starting antiretroviral therapy: Comparison of three different regimens - PREVALEAT II cohort. (August 2017) - Maggi, Paolo; Bellacosa, Chiara; Leone, Armando; Volpe, Anna; Ricci, Elena Delfina; Ladisa, Nicoletta; Cicalini, Stefania; Grilli, Elisabetta; Viglietti, Rosaria; Chirianni, Antonio; Bellazzi, Lara Ines; Maserati, Renato; et al.
Abstract: Background and aims: PREVALEAT (PREmature VAscular LEsions and Antiretroviral Therapy) II is a multicenter, longitudinal cohort study aimed at the evaluation of cardiovascular risk among advanced HIV-positive, treatment-naïve patients starting their first therapy. We hypothesized that these patients, present a higher cardiovascular (CV) risk. Methods: The study included all consecutive naïve patients with less than 200 CD4 cells/ml starting antiretroviral therapy. Our primary objective was to evaluate changes in carotid intima- media thickness (IMT). Secondary endpoints included changes in flow mediated vasodilation (FMD), inflammatory markers, triglycerides and cholesterol. Patients were evaluated at time 0, and after 3, 6 and 12 months. Results: We enrolled 119 patients, stratified into three different groups: patients receiving atazanavir/ritonavir boosted (ATV/r) based regimens, efavirenz (EFV) based regimens and darunavir/ritonavir boosted (DRV/r) based regimens. At baseline, advanced naïve patients showed a relevant deterioration of CV conditions in terms of traditional CV risk factors, endothelial dysfunction and serum biomarkers. During the 12-month follow up period, mean blood lipids significantly increased: total cholesterol from 159 to 190 mg/dL, HDL-C from 31 to 41 mg/dL, and LDL-C from 99 to 117 mg/dL. D-dimers steadily decreased (median level 624 at baseline and 214 at T3), whereas ICAM and VCAM consistently raised. DRV/r and ATV/r determined a more marked decrease of D-dimers as compared to EFV. Regarding the epi-aortic changes (IMT >1 mm or presence of atherosclerotic plaques), patients in the DRV/r group were at risk of developing pathological IMT during the study (OR 6.0, 95% CI 0.9–36.9), as compared to EFV ones. Conclusions: CV risk was elevated in advanced naïve patients and tended to remain high in the first year of therapy. Highlights: Advanced HIV-positive, treatment-naïve patients show a relevant deterioration of CV. During the first 12 months of therapy, flow mediated vasodilation (FMD), BMI and cholesterol significantly increase. In patients treated with protease inhibitor (PIs), values of D-dimers and hs-CRP significantly decrease. IMT and atherosclerotic plaques have a better outcome in patients treated with efavirenz (EFV). BMI tends to increase in all the groups, especially in the darunavir/ritonavir (DRV/r) one.